Risk factors of paclitaxel-induced peripheral neuropathy in patients with breast cancer: a prospective cohort study - Lixian, Sun; Xiaoqian, Yu; Luyan, Guo; Lizhi, Zhou; Rui, Du; Hongyue, Yao; Caijie, Zhao; Fenghui, Yuan (Frontiers in Oncology, 2024)
Objective Chemotherapy-induced peripheral neuropathy (CIPN) is a common and severe adverse reaction in taxane-based chemotherapy. This study aimed to analyze the risk factors of peripheral neuropathy in patients with breast cancer receiving paclitaxel chemotherapy to provide a reference for the early prevention of CIPN. Methods We included 350 patients with breast cancer who received chemotherapy for the first time at the Tangshan People’s Hospital between August 2022 and June 2023 and were followed for at least 3 months after the end of chemotherapy. The incidence of CIPN in patients with breast cancer was calculated, and risk factors for CIPN were analyzed using logistic regression analysis. Results The incidence rate of CIPN was 79.1%. Multifactor logistic regression analysis indicated that age ≥45 years [odds ratio (OR)=5.119, 95% confidence interval (CI)=1.395–18.780] and ≥60 years (OR=9.366, 95% CI=1.228–71.421), history of hypertension (OR=3.475, 95% CI=1.073–11.250), cumulative dose of chemotherapy drugs >900 mg (OR=4.842, 95% CI=1.961–5.946), vitamin D deficiency (OR=6.214, 95% CI=2.308–16.729), abnormal alanine aminotransferase (OR=3.154, 95% CI=1.010–9.844), anemia before chemotherapy (OR=2.770, 95% CI=1.093–7.019), infusion duration of chemotherapy drugs >30 min (OR=3.673, 95% CI=1.414–9.539), body mass index ≥24 kg/m2 (OR=8.139, 95% CI=1.157–57.240), mild depression (OR=4.546, 95% CI=1.358–15.223), and major depression (OR=4.455, 95% CI=1.237–16.037) increased the risk of CIPN. Having a regular caregiver (OR=0.223, 95% CI=0.087–0.573), high levels of physical activity (OR=0.071, 95% CI=0.008–0.647), and strong social support (OR=0.048, 95% CI=0.003–0.682) were protective factors against CIPN. Conclusion Clinical attention should be paid to patients with these risk factors, and active and effective preventive measures should be taken to reduce the occurrence of CIPN and improve the quality of life.